2017
DOI: 10.1016/j.drugalcdep.2017.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Sexual orientation, minority stress, social norms, and substance use among racially diverse adolescents

Abstract: Background Sexual minority adolescents are more likely than their heterosexual peers to use substances. This study tested factors that contribute to sexual orientation disparities in substance use among racially and ethnically diverse adolescents. Specifically, we examined how both minority stress (i.e., homophobic bullying) and social norms (i.e., descriptive and injunctive norms) may account for sexual orientation disparities in recent and lifetime use of four substances: tobacco, alcohol, marijuana, and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 26 publications
(36 reference statements)
1
35
0
Order By: Relevance
“…Adaptive personality traits (e.g., being ambitious, open to new experiences, less narcissistic) mitigated the adverse relationship between discrimination and alcohol misuse among SMY [49]. At least one study [38] found that connection to the sexual minority community was protective, while other studies either only found this association among a subset of SMY (e.g., gay-identified youth) or found no association at all [50, 51, 45, 52]. This inconsistency in findings may be partially explained by differences in peer group drinking norms [50, 53].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Adaptive personality traits (e.g., being ambitious, open to new experiences, less narcissistic) mitigated the adverse relationship between discrimination and alcohol misuse among SMY [49]. At least one study [38] found that connection to the sexual minority community was protective, while other studies either only found this association among a subset of SMY (e.g., gay-identified youth) or found no association at all [50, 51, 45, 52]. This inconsistency in findings may be partially explained by differences in peer group drinking norms [50, 53].…”
Section: Resultsmentioning
confidence: 99%
“…Parental attachment moderated cannabis risk among bisexual youth [10] and was associated with reduced overall drug use among Chinese young SMM involved in sex work [71]. In contrast, SMY community connectedness did not mitigate general drug use disparities [50, 51, 72, 52, 45], possibly due to differences in peer drug use norms [51]. Finally, policies at the state (e.g., employment non-discrimination; marriage equality) and school levels (e.g., anti-bullying) were associated with lower rates of both general drug and cannabis use [27], and drug-related consequences [31].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Previous studies have also documented higher lifetime rates of illicit drug use among LGB youth. [2][3][4][5][6][7] National surveys have found that LGB adults, especially women, are more likely to smoke, and to be heavy smokers, than heterosexual peers of the same gender. [8][9][10] Disparities in lifetime marijuana use and illicit drug use have also been observed among LGB adults.…”
Section: Introductionmentioning
confidence: 99%
“…The literature provides strong evidence for the impact of social norms on a variety of behaviors, including alcohol consumption (Padon, Rimal, Jernigan, Siegel, & DeJong, 2016; Pedersen et al, 2017; Rimal, 2008; Rimal & Mollen, 2013), tobacco use (Ali & Dwyer, 2009; Mead, Rimal, Ferrence, & Cohen, 2014; Mereish, Goldbach, Burgess, & DiBello, 2017), cannabis use (Ecker & Buckner, 2014; Mereish et al, 2017), healthy food consumption (Mollen, Rimal, Ruiter, & Kok, 2013), contraceptive use (Rimal & Lapinski, 2015), and HIV testing (Batona, Gagnon, Simonyan, Guedou, & Alary, 2015). Findings on the role of norms do vary, however.…”
mentioning
confidence: 99%